1997
DOI: 10.1007/bf02407560
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of stem water potential in field grown potatoes using stem psychrometers

Abstract: SummaryThe first large scale outdoor measurements of potato (Solanum tuberosum L.) stem water potential (SWP) using in sittt temperature-corrected stem psychrometers were performed on three cultivars common to Ontario, Canada (Atlantic, Monona and Norchip). Potato plants were examined under three soil water treatments which included rainfed, irrigated and stressed through the use of rain shelters. Cultivar variations in SWP under both irrigated and rainfed conditions were slight (P>0.05), although some signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The overall trend in RT based on the AWD is similar to that observed for corn (Ritchie 1973;Muchow and Sinclair 1991), sorghum and cotton (Rosenthal et al 1987). Studying the same three cultivars, Coffey et al (1997), found little variation in the dirunal pattern of stem water potential under well-watered conditions. However, with increasing AWD, differences were observed.…”
Section: Sap Flow As Affected By Soil Water Solar Radiation and Humisupporting
confidence: 70%
See 1 more Smart Citation
“…The overall trend in RT based on the AWD is similar to that observed for corn (Ritchie 1973;Muchow and Sinclair 1991), sorghum and cotton (Rosenthal et al 1987). Studying the same three cultivars, Coffey et al (1997), found little variation in the dirunal pattern of stem water potential under well-watered conditions. However, with increasing AWD, differences were observed.…”
Section: Sap Flow As Affected By Soil Water Solar Radiation and Humisupporting
confidence: 70%
“…Irrigation water was applied generally twice weekly to maintain root zone soil water within 25% of the upper limit of available water. Manual rain shelters were constructed to provide protection from selected rainfall events for the sheltered plots (Coffey et al 1997). Prior to forecasted rain, polyethelene covers were placed over wooden stakes to divert rainfall from the canopy to trenches that directed rain water away from the plots.…”
mentioning
confidence: 99%
“…The results indicate for Atlantic an AWD s value of approximately 30% compared to 16% for Norchip and 4% for Monona. Coffey et al (1997) found stem water potentials for the same cultivars to have similar differences in their response to soil water. In studying the cultivar Maris Piper, Jefferies (1989) indicated that the leaf extension rate was reduced when 13% of the root zone available water was depleted.…”
Section: Resultsmentioning
confidence: 64%
“…Jefferies (1989) estimated this value to be -1.1 MPa. This difference could be due to cultivar response to soil water status as found by Coffey et al (1997) under identical environmental and soil physical conditions. These variations among cultivars also extend to leaf expansion (Jefferies, 1993b).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation